2020
DOI: 10.1145/3411749
|View full text |Cite
|
Sign up to set email alerts
|

From Appearance to Essence

Abstract: Truth discovery has been widely studied in recent years as a fundamental means for resolving the conflicts in multi-source data. Although many truth discovery methods have been proposed based on different considerations and intuitions, investigations show that no single method consistently outperforms the others. To select the right truth discovery method for a specific application scenario, it becomes essential to evaluate and compare the performance of different methods. A drawback of current research effort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Based on these two fundamental assumptions, researchers have proposed numerous truth discovery algorithms. Methods for truth discovery are categorized into two types: single-truth discovery methods [5][6] and multi-truth discovery methods [7][8]. Some methods merge the two [9].…”
Section: Related Workmentioning
confidence: 99%
“…Based on these two fundamental assumptions, researchers have proposed numerous truth discovery algorithms. Methods for truth discovery are categorized into two types: single-truth discovery methods [5][6] and multi-truth discovery methods [7][8]. Some methods merge the two [9].…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, they showed that the regression method is sensitive to the number of training samples. For China, there is little ground truth data available on irrigation [25]. Hence, we decided to use the agreement-scoring method to create a synergy irrigation map for China.…”
Section: Synergy Approach To Creating Irrigation Mapsmentioning
confidence: 99%